2019
DOI: 10.3390/su11010186
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Analysis of Behind-the-Meter Energy Storage System According to Public Policy on an Electricity Charge Discount Program

Abstract: Energy storage systems are crucial in dealing with challenges from the high-level penetration of renewable energy, which has inherently intermittent characteristics. For this reason, various incentive schemes improving the economic profitability of energy storage systems are underway in many countries with an aim to expand the participation rate. The electricity charge discount program, which was introduced in 2015 in Korea, is one of the policies meant to support the economic feasibility of demand-side energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Countries such as the U.S., Korea, Japan, and Germany, which are striving to expand PV energy, are implementing policies to expand ESS simultaneously [36,41]. In particular, the grid-scale ESS is led by Europe, China, and U.S. while behind-the-meter ESS is led by South Korea, Europe, and China [3].…”
Section: Efforts To Promote Ess For Increase Pv Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…Countries such as the U.S., Korea, Japan, and Germany, which are striving to expand PV energy, are implementing policies to expand ESS simultaneously [36,41]. In particular, the grid-scale ESS is led by Europe, China, and U.S. while behind-the-meter ESS is led by South Korea, Europe, and China [3].…”
Section: Efforts To Promote Ess For Increase Pv Generationmentioning
confidence: 99%
“…The Korean government has pursued policies of ESS diffusion throughout the power system: Frequency regulation and distribution network reinforcement, renewable energy integration, peak management, and electricity bill reduction. These policies are commonly aimed at improving the system's flexibility and increasing its capability [41]. The policies have also contributed to the expansion of ESS in Korea.…”
Section: Dissemination Of Ess For Pv Integrationmentioning
confidence: 99%
“…These were (i) avoiding distribution/transmission for transport of energy and (ii) selling and buying energy at different times. In [6] , Byuk Keun Jo and team evaluated the impact of an incentive scheme for behind the meter ESS called electricity charge discount program in South Korea. Based on a case study that was carried out to study the impact of the program, the profitability of behind the meter ESS showed tremendous improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies evaluated an economic analysis of rooftop PVs with BESS by applying the discounted cash flow, net-present value (NPV), return on investment, and levelized cost of energy [13,14]. Furthermore, an economic analysis of the BESS under the BTMS with an electricity charge discount policy has been proposed [15], as well as some analysis of the demand charge reduction [16,17]. However, the studies on the SPPA and solar leasing agreement are limited.…”
Section: Introductionmentioning
confidence: 99%